2015
DOI: 10.1097/qad.0000000000000512
|View full text |Cite
|
Sign up to set email alerts
|

Combination antiretroviral therapy reduces the detection risk of cervical human papilloma virus infection in women living with HIV

Abstract: cART significantly reduced cervical HPV infection. This effect was dependent on the duration of exposure to cART and is the mechanism by which cART may improve the outcome of dysplasia in HIV-infected women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 31 publications
1
30
0
2
Order By: Relevance
“…Moreover, immune defects associated with HIV infection probably contribute to the HPV pathogenesis by preventing spontaneous clearance of HPV [6]. A recent study found that in WLWH every month on HAART reduced the detection risk of any cervical HPV infection by 9 % [30]. Likewise, short duration of HAART predicted HPV in the current study.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Moreover, immune defects associated with HIV infection probably contribute to the HPV pathogenesis by preventing spontaneous clearance of HPV [6]. A recent study found that in WLWH every month on HAART reduced the detection risk of any cervical HPV infection by 9 % [30]. Likewise, short duration of HAART predicted HPV in the current study.…”
Section: Discussionsupporting
confidence: 55%
“…Nine candidate predictor variables were chosen a priori due to current knowledge on risk factors of HPV [6, 30, 31]; age (18–29, 30–50 and >50 years of age), race, age at sexual debut (<16 versus ≥ 16 years of age), HAART duration (years on HAART), AIDS prior to inclusion, smoking status, number of lifetime sexual partners (<5 versus ≥ 5), use of hormonal contraceptives, and CD4 count at inclusion (<200, ≥200-349 and ≥350 cells/μL).…”
Section: Methodsmentioning
confidence: 99%
“…A previous study by Palefsky (9) evaluated whether the use of cART has an influence on the prevalence of anal HPV infection by immune recovery, finding that it lead to a limited reduction in HPV prevalence and the regression of cervical intraepithelial neoplasia. Subsequently, it was demonstrated that the risk of persistent HPV infection in HIV-infected women under long-term cART was reduced due to sustained viral suppression and increased CD4 counts (34,35). The relatively short duration of cART use in the present study did not have a significant effect on anal HPV reduction.…”
Section: Discussionmentioning
confidence: 47%
“…Regarding the prevalence of different HPV genotypes in the cervix and anus, 13 high-risk HPV genotypes (16,18,31,33,35,39,45, 51, 52, 56, 58, 59 and 68) and 11 low-risk HPV genotypes (6,11,44, 53, 54, 66, 69, 70, 71, 74 and 82) were found. Fig.…”
Section: Cervical and Anal Hpv Findingsmentioning
confidence: 99%
“…Our finding is similar to reports that have shown no protective effect of ART on HPV clearance 33,34 and contrary with studies that show greater HPV clearance with the institution of ART. 3537 …”
Section: Discussionmentioning
confidence: 99%